FINAL YEAR STUDENTS’ PERFORMANCE IN COMMUNICATION SKILLS OSCE IN A MALAYSIAN MEDICAL SCHOOL - Chan Sook Ching; Sandheep S; Lee SL (Asian Journal of Medicine & Health Sciences, 2018)
Introduction: The Royal College of Medicine Perak under Universiti Kuala Lumpur started its own undergraduate medical degree programme in 2007. As part of the review and evaluation of communication skills (CS) training, the performance of the two pioneer batches of final year students in CS Objective Structured Clinical Examinations (OSCEs) stations in the 2012 and 2013 were analysed. Methods: The CS OSCE stations were analysed based on the percentage of students obtaining a satisfactory performance in each CS component. Overall performance in each CS component was considered satisfactory, if ≥ 50% of students achieved satisfactory performance or unsatisfactory, if < 50% of students achieved satisfactory performance. The two cohorts were compared for any significant statistical difference (p < 0.05) in their performance. Results: Satisfactory performance was obtained in basic CS (courtesy, appropriate non-verbal and verbal CS), stating intention of session, recognizing patient’s cues, checking and addressing patient’s perceptions and concerns, checking patient’s understanding, breaking bad news and maintaining a professional attitude. The performance was unsatisfactory in assessing prior knowledge, discussing patient management and checking patient’s coping skills. Both the two cohorts’ performance did not differ significantly. Conclusion: Overall the students’ performance was satisfactory except for assessing prior knowledge, discussing management and checking patients’ coping skills.